2022
DOI: 10.2340/jrm.v54.2238
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Participation Post-Stroke: Longitudinal Assessment of Community Participation, Positive Affect, Social Support and Functional Independence

Abstract: Objective: To investigate longitudinal, predictive associations between community participation, positive affect, social support, and functional independence for individuals post-stroke at 3 and 12 months post-discharge.Design: Longitudinal design.Subjects: Data from 544 participants were obtained from the Stroke Recovery in Underserved Populations (2005–06) database.Methods: A cross-lagged panel network analysis to identify the complex set of predictive relationships between community participation, positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…One quantitative study recently showed that positive affectparticularly feelings of happiness-reported by post-stroke patients 3 months after discharge from a rehabilitation hospital played an impor-tant role in predicting social participation 1 year after discharge. When separated from the participants with no aphasia, this predictive association was even stronger for PWA (Ashaie & Castro 2022). Similarly, qualitative findings have shown that PWA often mention a positive outlook as helping them cope with the challenges of aphasia and facilitating social participation (Brown et al 2012;Harmon 2020;Le Dorze et al 2014).…”
Section: Influence Of Emotion On Language Processing In Aphasiamentioning
confidence: 88%
See 1 more Smart Citation
“…One quantitative study recently showed that positive affectparticularly feelings of happiness-reported by post-stroke patients 3 months after discharge from a rehabilitation hospital played an impor-tant role in predicting social participation 1 year after discharge. When separated from the participants with no aphasia, this predictive association was even stronger for PWA (Ashaie & Castro 2022). Similarly, qualitative findings have shown that PWA often mention a positive outlook as helping them cope with the challenges of aphasia and facilitating social participation (Brown et al 2012;Harmon 2020;Le Dorze et al 2014).…”
Section: Influence Of Emotion On Language Processing In Aphasiamentioning
confidence: 88%
“…In one study, for example, individual responses varied across PWA with approximately half to two-thirds showing signs of interference, whereas others showed the Although the previous section highlighted short-term outcomes of emotional responses on language processing, this section emphasizes longer-term outcomes on social participation. In addition to impacting language processing, emotion can affect social participation for PWA (Ashaie & Castro 2022;Baker et al 2019;Brown et al 2012;Harmon 2020;Hilari et al 2010;Le Dorze et al 2014;Manning et al 2022). My definition of social participation is taken from Levasseur and colleagues (2010) who, after analyzing 43 interdisciplinary definitions including from aphasiology, concluded that "social participation can be defined as a person's involvement in activities that provide interaction with others in society or the community" (p. 2148).…”
Section: Influence Of Emotion On Language Processing In Aphasiamentioning
confidence: 99%
“…However, family members and peers are also important sources of psychosocial support both in the inpatient setting and as clients reintegrate into the community. Social support has been shown to be an important factor for psychological wellbeing and participation post‐stroke (Ashaie & Castro, 2022), with connectedness as an integral component (Haun et al., 2008). Interpersonal connections with peers can instil hope and resilience (Sadler et al., 2017) to engage in the rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
“…Several international reviews and both cross-sectional and longitudinal studies highlight the decline in activity performance and participation of people who have suffered a stroke [ 6 , 7 , 8 , 9 , 10 , 11 ]. The scientific literature indicates that contextual factors, including socioeconomic environmental factors and personal factors, such as age and gender, are significant predictors of functional recovery in this population [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature indicates that contextual factors, including socioeconomic environmental factors and personal factors, such as age and gender, are significant predictors of functional recovery in this population [ 12 , 13 ]. Furthermore, functional recovery appears to be closely related to the previous level of performance and participation [ 9 , 11 , 14 ] and to the extent and severity of deficits in motor, sensory, and cognitive functions [ 6 , 8 , 14 ]. Therefore, the interdisciplinary intervention proposals aim at improving function, performance, and participation.…”
Section: Introductionmentioning
confidence: 99%